El Salvador Financial Sector Assessment Program Development Module : Financial Infrastructure - World Bank (World Bank, Washington, DC, 2017)
This note was prepared in the context of a World Bank Financial Sector Assessment Program (FSAP) mission in El Salvador in March 2016. Since the last FSAP, the national payments system (NPS) has consolidated and expanded. The real-time gross settlement (RTGS) systems owned and operated by the Banco Central de Reserva de El Salvador (BCR) is the backbone of the NPS and is widely subscribed by both banks and supervised non-bank financial institutions. In 2013, the BCR launched a service for government disbursements called Sistema de Pagos Masivos (SPM). ATM and POS terminal deployment in El Salvador is below the average for the Latin America and the Caribbean, but above the average for lower-middle income countries. Notwithstanding these positive developments, the payments system remains exposed to certain risks and presents areas of inefficiency that the BCR aims to address comprehensively and in stages through a revised national payment system strategy. The note contains technical analysis and detailed information underpinning the FSAP assessment’s findings and recommendations. Further information on the FSAP program can be found at www.worldbank.org/fsap.